Evaluation of the removal and effects of Cylindrospermopsin on ripened slow sand filters - Valencia-Cárdenas, Daniel (2023)
The occurrence of toxic blooms of cyanobacteria has been a matter of public health interest due to the cyanotoxins produced by these microorganisms. Cylindrospermopsin (CYN) is a cyanotoxin of particular concern due to its toxic effects on humans. This study investigated the removal and effects of CYN in ripened slow sand filters (SSFs) treating water from Paranoá Lake, Brasilia, Brazil. Four pilot-scale SSFs were ripened and operated for 74 days. Two contamination peaks with CYN were applied along the filtration run. The improvement of any of the evaluated water quality parameters was not affected by the presence of CYN in the raw water. The SSFs efficiently removed CYN, presenting concentrations lower than 0.8 µg/L in the filtered water. The microbiota of the SSFs were dominated by protozoa of the genus Euglypha and amoebas of the genera Arcella, Centropyxis, and Amoeba, together with some groups of rotifers. These microorganisms played a crucial role in removing total coliforms and E. coli. In addition, CYN was not identified as a determining factor in the microbiota composition.